2021
DOI: 10.48550/arxiv.2112.14919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictions for the X-ray circumgalactic medium of edge-on discs and spheroids

Anna Nica,
Benjamin D. Oppenheimer,
Robert A. Crain
et al.

Abstract: We investigate how the X-ray circumgalactic medium (CGM) of present-day galaxies depends on galaxy morphology and azimuthal angle using mock observations generated from the EAGLE cosmological hydrodynamic simulation. By creating mock stacks of eROSITAobserved galaxies oriented to be edge-on, we make several observationally-testable predictions for galaxies in the stellar mass range 𝑀 β˜… = 10 10.7βˆ’11.2 M . The soft X-ray CGM of disc galaxies is between 60 and 100% brighter along the semi-major axis compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Third, recent studies have shown that the extended hot gas atmosphere can significantly impact the total observed luminosity depending on the chosen projection radius (Nica et al 2022;Comparat et al 2022). In Comparat et al (2022) in the energy range 0.5-10 keV.…”
Section: Gas Luminosity Scaling Relationmentioning
confidence: 99%
“…Third, recent studies have shown that the extended hot gas atmosphere can significantly impact the total observed luminosity depending on the chosen projection radius (Nica et al 2022;Comparat et al 2022). In Comparat et al (2022) in the energy range 0.5-10 keV.…”
Section: Gas Luminosity Scaling Relationmentioning
confidence: 99%